Predetermination and Identification of Failure Modes Related to a Welded Car Chassis Component - Ana-Maria Bogatu; Dumitru-Titi Cicic; Mihăiță-Nicolae Coman; Corneliu Rontescu; Alexandru-Vasile Oancea (Romanian Journal of Transport Infrastructure)
Failure Mode and Effects Analysis (FMEA) is a method commonly used in activities with the main objective of finding measures to improve manufacturing processes or products, by identifying actual and potential ways in which components fail or processes malfunction. The paper presents the practical application of the FMEA method for the process of obtaining an important component of the resistance system of a motor vehicle, namely a chassis. Some general information is presented on the importance of the FMEA method, the product analyzed, followed by the practical application of the method, starting from the determination of the probable causes of failure and their effects on: the organization, the customer and the end user. The processes carried out to obtain the chassis are identified and for a category of processes the Severity (S), Occurrence (O), Detection (D) and Risk Priority Number (RPN) indicators are calculated. Also, the preventive control methods and the control methods to be applied to reduce the occurrence of the defect are identified and indicated.